2020
DOI: 10.3389/fchem.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding Needle Flower Structure CuCo2S4 on Carbon Cloth for Flexible High Energy Supercapacitors With the Gel Electrolyte

Abstract: A facile hydrothermal approach was adopted to the direct synthesis of bimetallic sulfide (CuCo 2 S 4 ) on carbon cloth (CC) without binders for the supercapacitor's electrodes. A possible formation mechanism was proposed. The prepared bimetallic electrode exhibited a high specific capacitance (Csp) of 1,312 F·g −1 at 1 A·g −1 , and an excellent capacitance retention of 94% at 5 A·g −1 over 5,000 cycles. In addition, the asymmetric supercapacitor (CuCo 2 S 4 /CC//AC/CC) exhibited energy density (42.9 wh·kg −1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…At high scan rate, the OH − ions can access only the outer active sites of the electrode due to short interval and because of the low utilization of active materials shifting in peaks occurs. The possible mechanism of interaction of OH − may be as follows in equation (1–3) [18] CuCo2S4+2OH-CuCo2S4(OH-)​2+2e-1 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr Cu{Co}_{2}{S}_{4}{\rm \ }+2O{H}^{-}{\rm \ }{\rm \ }\leftrightarrow \hfill\cr Cu{Co}_{2}{S}_{4}(O{H}^{-}{)}_{2}+2{\rm \ }{e}^{-1}{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }\hfill\cr}}$ CoSOH+OH-CoSO+H2O+e-1 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr CoSOH+{\rm \ }O{H}^{-}{\rm \ }\leftrightarrow CoSO+{\rm \ }{H}_{2}O+{\rm \ }{e}^{-1}{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }\hfill\cr}}$ CuSOH+OH-CuSO+H2O<...…”
Section: Resultsmentioning
confidence: 99%
“…At high scan rate, the OH − ions can access only the outer active sites of the electrode due to short interval and because of the low utilization of active materials shifting in peaks occurs. The possible mechanism of interaction of OH − may be as follows in equation (1–3) [18] CuCo2S4+2OH-CuCo2S4(OH-)​2+2e-1 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr Cu{Co}_{2}{S}_{4}{\rm \ }+2O{H}^{-}{\rm \ }{\rm \ }\leftrightarrow \hfill\cr Cu{Co}_{2}{S}_{4}(O{H}^{-}{)}_{2}+2{\rm \ }{e}^{-1}{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }\hfill\cr}}$ CoSOH+OH-CoSO+H2O+e-1 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr CoSOH+{\rm \ }O{H}^{-}{\rm \ }\leftrightarrow CoSO+{\rm \ }{H}_{2}O+{\rm \ }{e}^{-1}{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }{\rm \ }\hfill\cr}}$ CuSOH+OH-CuSO+H2O<...…”
Section: Resultsmentioning
confidence: 99%
“…The possible redox reactions responsible for CePO 4 @CuCo 2 S 4 /NF are as follows (eqs –): ,, The GCD curves of CeO 2 /NF, CePO 4 /NF, and CuCo 2 S 4 /NF electrodes at different densities are exhibited (Figure S6a–c). In order to further highlight the advantages of CePO 4 @CuCo 2 S 4 active material and reduce the water decomposition reaction during the low current density measurement, 6 M KOH electrolyte is used for testing, thus the voltage window of GCD measured in CePO 4 @CuCo 2 S 4 electrode materials is the most appropriate voltage window at 0∼0.3 V. All GCD curves of CeO 2 /NF, CePO 4 /NF, and CuCo 2 S 4 /NF electrodes reveal approximately symmetrical charge–discharge times at different current densities, which means that they have good reversibility of charging and discharging process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Zhu and Zheng developed Co 3 O 4 anchored on g-C 3 N 4 by the chemical precipitation route and obtained excellent performance including a specific capacitance of 780 F g –1 at 1.25 A g –1 with a retention of 80% after 1000 cycles in 2 M KOH . Xie et al fabricated an asymmetric supercapacitor based on the CuCo 2 S 4 /CC needle flower structure and reported an energy density of 42.9 W h kg –1 at 0.8 kW kg –1 with a specific capacitance retention of 80% after 5000 GCD cycles . Shao et al reported the binder-free Co 3 (PO 4 ) 2 ·8H 2 O electrode material, prepared by the hydrothermal route for the supercapacitor application.…”
Section: Introductionmentioning
confidence: 99%
“…37 Xie et al fabricated an asymmetric supercapacitor based on the CuCo 2 S 4 /CC needle flower structure and reported an energy density of 42.9 W h kg −1 at 0.8 kW kg −1 with a specific capacitance retention of 80% after 5000 GCD cycles. 38 Shao et al reported the binder-free Co 3 (PO 4 ) 2 •8H 2 O electrode material, prepared by the hydrothermal route for the supercapacitor application. They had obtained a specific capacitance of 111.2 F g −1 with a specific energy of 29.29 W h kg −1 at a specific power of 4687 W kg −1 using the supercapacitor device.…”
Section: ■ Introductionmentioning
confidence: 99%